Visit to climate smart farm sites in Western Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In May 2014, CCAFS East Africa team visited the climate-smart site farmers in Western Kenya. These are some of the photos from that trip. Photos: C. Schubert (CCAFS)